THE PAINTING OF DIFFERENT ART DIRECTIONS AS A SOURCE FOR CREATING CLOTHING COLLECTIONS - KRASNIUK, L. V.; TROYAN, O. M.; YEMETS, O. V. (Art and Design, 2023)
The aim of this research is to analyze various approaches to the development of the creative concept for the author’s clothing collections of different styles which are designed on the basis of such sources of inspiration as paintings. Methodology. The basic principles of the systematic approach to artistic design of the author couture collection such as literaryanalytical research and associative stylization of the source of creativity were used in the process. Results. It is revealed that producing an interesting image in the costume is a creative process of developing a complex system «individual-image-costume» which reflects modern trends in designing. The article shows that the development of the creative concept envisages the choice of the inspiration source which occupies the central place in the artistic designing of the author’s clothing collections. It is emphasized that for many clothes designers it is paintings created by the well-known artists that are the most interesting and fruitful source of inspiration. The article presents the art analysis of paintings from such artistic directions as neoplasticism, primitivism and graphic art. The principles of formation of the author’s clothing collections according to the paintings as the source of inspiration are considered. Different approaches to the production of the creative concept are demonstrated. The scientific novelty. The paper sets out the basic artistic and compositional features of paintings from such artistic directions as neoplasticism, primitivism and graphic art (forms, decorative elements and color combinations) and their application in the design of collections of modern fashionable clothes. The practical significance of the study consists in the design and execution of author’s collections of women’s clothing using the artistic and compositional features of paintings and taking into account modern fashion trends. The materials of this study can also be reflected in lecture courses in the disciplines of «Composition of products», «Design of artistic systems» and «Style and image in the fashion industry».